Importância da broncoscopia flexível na decanulação dos pacientes traqueostomizados - Leonardo Brand Rodrigues (2012)
Tracheostomy is a procedure performed frequently and theirprolonged can cause laryngotracheal changes in up to 65% of patients. The criteria employed in decannulation are usually neglected and few if any investigative data exist to inform evidence-based care. Objective: To evaluate patients undergoing tracheostomy decannulation with bronchoscopy, the incidence and types of laryngotracheal injury, factors that influence the decannulation, comparing the clinical tests with the diagnosis of laryngotracheal injury to the bronchoscopy and evaluating the effectiveness of clinical criteria of decannulation. Methods: We analyzed 51 patients whose ages ranged from 19 to 87 years, 26males and 25 females, evaluated by a multidisciplinary team, who met clinical criteria for decannulation. All patients underwent occlusion of the tracheostomy tube for 24 hours, regardless of tolerance, underwent flexible bronchoscopy and laryngotracheal injuries described, diagnosed and classified. We compared the clinical indication criteria for decannulation with the diagnosis of laryngotracheal injury to the bronchoscopy contrary to it. We identified the factors that couldinterfere with decannulation and assessed the importance of bronchoscopy as part of the process. Results: Of 51 patients, 40 (80.4%) had laryngotracheal injury. Of these 40 fit for decannulation by clinical evaluation, eight (20%) had bronchoscopic laryngotracheal lesions that contraindicated procedure, which is significantly higher than the 5% failure rate reported in the literature (p = 0.0007). There was no effect of age, gender, complications related to tracheostomy or diseases that led to intubation or tracheostomy in decannulation. Among diseases, only diabetes mellitus showed a significant relationship with the resence of bronchoscopic laryngotracheal injuries that contraindicated ecannulation (p =0.037). Analyzed separately, the period of plastic stent was significantly correlated with the diagnosis of lesions that contraindicate decannulation (p = 0.038). However, when analyzing the group of variables with the time adjustment by multiple logistic regression, no variable showed significance. Conclusion: based on this research on the influence of fiberoptic bronchoscopy in tracheostomy decannulation of patients, we can say that it was the high incidence of laryngotracheal injury diagnosed by bronchoscopy. Among the factors that couldinterfere with decannulation, only diabetes mellitus manifested more likely to contraindication of decannulation by bronchoscopy. Bronchoscopy increased safety process, since no patient required a new cannulation, demonstrating that clinical evaluation associated with occlusion of the tracheostoma was not enough to properly indicate decannulation.